2022
DOI: 10.31643/2022/6445.06
|View full text |Cite
|
Sign up to set email alerts
|

Smelting options for carbon ferrochrome based on ore raw materials, middlings and their technological evaluation

Abstract: The article presents the results of large-scale laboratory tests carried out in the conditions of the Chemical and Metallurgical Institute named after V.I. Zh. Abishev on the use of briquetted mono-charge in the smelting of carbon ferrochrome on a 250 kVA furnace. The purpose of these studies was to determine the technological parameters of the use of briquetted mono-charge containing in its composition chrome ore, wastes from the production of high-carbon ferrochrome, middlings and various carbonaceous reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The following composite components were used as a source for the synthesis of a new type of binder: the mineral part of refined ferrochromium slag (source of CaO and SiO 2 ), ferruginous forms of diatomite (source of SiO 2 and FeO), fine coke (source of SiO 2 , pellet heating temperature controller-pulverized screening of special coke of Sary-Arka Spetskoks LLP Coke Plant), an aqueous solution of liquid glass (binder) [19]. Refined ferrochrome slag (RFS) is a dry pulverized mass with metallic inclusions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following composite components were used as a source for the synthesis of a new type of binder: the mineral part of refined ferrochromium slag (source of CaO and SiO 2 ), ferruginous forms of diatomite (source of SiO 2 and FeO), fine coke (source of SiO 2 , pellet heating temperature controller-pulverized screening of special coke of Sary-Arka Spetskoks LLP Coke Plant), an aqueous solution of liquid glass (binder) [19]. Refined ferrochrome slag (RFS) is a dry pulverized mass with metallic inclusions.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of [19] present the results of a study on the sintering of chromite fines with the determination of the influence of such factors as the dispersion and dosage of coke fines, the moisture content of the sinter charge and the duration of ignition on the efficiency of sintering of fine chromite. It is shown that the sintering of chromite fines is characterized by a higher sintering temperature (1450-1500 • C) and a longer cooling time compared to iron ores.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is shown that the recovery process is controlled by the process diffusion, and the activation energy ranges from 61.5 to 72.25 kJ/mol. In other studies [16], the kinetics and mechanism of reduction of agglomerates are studied using traditional types of reducing agents.…”
Section: Introductionmentioning
confidence: 99%